Performance of reinforced concrete beams externally prestressed with fiber composites - Mukherjee, Abhijit; Rai, G. (Elsevier BV, 2009)
This paper presents the results of an experimental study to investigate the flexural behavior of reinforced concrete (RC) beams that have reached their ultimate bearing capacities and then retrofitted with externally prestressed carbon fiber reinforced composite (CFRC) laminates. The effect of variation in prestressing force on CFRC laminates bonded to the RC beam is investigated in terms of the flexural strength, deflections, cracking behavior and failure modes. The results indicate that rehabilitation of significantly cracked beams by bonding CFRC laminates is structurally efficient.